2007
DOI: 10.1088/0953-4075/40/21/008
|View full text |Cite
|
Sign up to set email alerts
|

Shifts and broadenings of barium Rydberg states perturbed by inert gases

Abstract: Collisional broadening and shift data for even parity states of neutral barium are presented. A two-photon absorption technique is used to populate Rydberg states of nd 1 D 2 , 3 D 2 and 1 S 0 series. High-resolution Ba excitation spectra were measured using a diode detector while scanning the frequency of an excimer pumped dye laser. Inert gases Ar, Kr and Xe were used as perturbers at pressures ranging from 10 mb to 400 mb. Shifts and broadenings of spectral lines were measured as a function of pressure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Two-photon excitations to some of the allowed levels within these configurations could not be recorded either because of low oscillator strengths and weak signals or due to the unavailability of suitable laser dyes beyond the spectral range of 400-650 nm. Shift and broadening rates due to collisions with inert gas perturbers (Ar, Kr and Xe) belonging to the singly excited Rydberg series have recently been published [12]. That study showed that the shifts and the broadenings as a function of inert gas pressure in the cell remains linear over the range of 10-300 mbar pressure of Ar, Kr and Xe gases.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Two-photon excitations to some of the allowed levels within these configurations could not be recorded either because of low oscillator strengths and weak signals or due to the unavailability of suitable laser dyes beyond the spectral range of 400-650 nm. Shift and broadening rates due to collisions with inert gas perturbers (Ar, Kr and Xe) belonging to the singly excited Rydberg series have recently been published [12]. That study showed that the shifts and the broadenings as a function of inert gas pressure in the cell remains linear over the range of 10-300 mbar pressure of Ar, Kr and Xe gases.…”
Section: Resultsmentioning
confidence: 96%
“…[7], forced autoionization [8][9][10] and hyperfine structures of alkaline earths [11]. Our recent study [12] of collision induced shifts and broadenings of Rydberg states of the 6snl series of Ba by inert gas perturbers also showed several examples where these interconfiguration interactions are responsible for anomalies and deviations from expected values. This has motivated us to measure the shift and broadening parameters for those important interacting perturbers belonging to the 5dns (n = 7, 8), 5dnd (n = 6, 7) and 6p 2 doubly excited configurations.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Our laboratory has been active in the area of collisional effects on line shapes. Following our earlier study of line shifts and broadenings in barium Rydberg states [6], we present here the data on calcium. Astrophysical importance of Ca is well known due to its abundance in the sun as well as other late-type stars.…”
Section: Introductionmentioning
confidence: 99%